Cobalt molybdenum / magnesium aluminum metal catalyst, preparation method and application thereof, and preparation method of carbon nanotube

By using small-molecule organic acids and modifiers to prepare cobalt-molybdenum/magnesium-aluminum metal catalysts, the problems of insufficient catalyst stability and performance have been solved, enabling the efficient preparation of small-diameter, high aspect ratio carbon nanotubes, reducing costs, and making them suitable for industrial applications.

CN120838429APending Publication Date: 2025-10-28XIAMEN KNANO GRAPHENE TECH CORP +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511006472.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In the process of preparing carbon nanotubes, the existing technology suffers from insufficient structural stability and catalytic performance of the catalyst, resulting in low yield, large tube diameter, poor aspect ratio, and high preparation cost, making it difficult to achieve industrial production.

Method used

Small molecule organic acids were used as chelating agents, combined with modifiers such as propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and chitosan, to prepare cobalt-molybdenum/magnesium-aluminum metal catalysts. Stable cobalt-molybdenum/magnesium-aluminum metal oxides were formed by the sol-gel method and used for the preparation of carbon nanotubes by chemical vapor deposition.

Benefits of technology

This improved the structural stability and catalytic performance of the catalyst, resulting in small-diameter, high aspect ratio oligowalled carbon nanotubes, which reduced the preparation cost and made them suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120838429A_ABST
    Figure CN120838429A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of carbon nanomaterials, and relates to a cobalt molybdenum / magnesium aluminum metal catalyst, a preparation method and application thereof, and a preparation method of a carbon nanotube. The preparation method of the cobalt molybdenum / magnesium aluminum metal catalyst comprises the following steps: S1, carrying out chelation reaction on metal salt and small molecular organic acid in a solvent, adjusting the pH value of the obtained chelation product to 3-7.5, and mixing the chelation product with a modifier to form gel; and S2, roasting the gel to obtain the cobalt molybdenum / magnesium aluminum metal catalyst. The preparation method is characterized in that in the preparation process of the cobalt-molybdenum / magnesium-aluminum metal catalyst, small-molecular organic acid is used as a chelating agent, and a specific modifier is used as an accelerant and a stabilizer, so that the prepared cobalt-molybdenum / magnesium-aluminum metal oxide has good structural stability and catalytic performance, and when the cobalt-molybdenum / magnesium-aluminum metal oxide is used as a carbon nanotube synthesis catalyst, the catalytic performance of the catalyst is greatly improved. Not only can the carbon yield be improved, but also the few-walled carbon nanotube with small tube diameter and high length-diameter ratio can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon nanomaterials, specifically relating to a cobalt-molybdenum / magnesium-aluminum metal catalyst, its preparation method and application, and a method for preparing carbon nanotubes. Background Technology

[0002] Carbon nanotubes are seamless tubular structures formed by tightly coiling single or multiple layers of graphene sheets around a central axis at a specific helical angle. Based on the number of graphene layers, they are meticulously classified into single-walled carbon nanotubes and multi-walled carbon nanotubes. Currently, carbon nanotube materials are mainly used as conductive additives in new energy batteries. Highly efficient conductive slurries are prepared by meticulously mixing carbon nanotubes with solvents, dispersants, and other raw materials, followed by stirring and grinding. Compared to traditional conductive agents such as carbon black and conductive graphite, carbon nanotubes, with their unique hexagonal network structure, exhibit superior electrical and thermal conductivity, as well as excellent acid and oxidation resistance. These properties are crucial for improving the cycle stability, energy density, and fast charge / discharge capability of lithium batteries. Therefore, carbon nanotubes have been widely adopted in the manufacture of high-performance power lithium batteries. When evaluating the conductivity of carbon nanotubes, the aspect ratio is a crucial indicator, directly affecting the performance of carbon nanotube products. Specifically, a smaller diameter and a longer length not only enhance the thermal conductivity along the axial direction of the carbon nanotube but also further improve its conductivity. It is worth noting that fewer-walled carbon nanotubes exhibit superior electrical conductivity compared to multi-walled carbon nanotubes, while requiring less material and offering better safety.

[0003] The preparation methods for carbon nanotubes encompass a variety of approaches, including chemical vapor deposition (CVD), laser evaporation, arc discharge, and hydrothermal / solvothermal synthesis. Among these, CVD has become the mainstream choice in the industry due to its advantages of moderate operating temperature, ease of control, and high-yield production of high-purity carbon nanotubes. Currently, most metal catalysts used in the preparation of ultrafine carbon nanotubes via CVD employ metal oxides such as alumina and magnesium oxide as supports, typically prepared using impregnation or hydrothermal synthesis methods.

[0004] The current optimal strategy for obtaining low-diameter carbon nanotubes is to prepare catalysts with stable metal nanoparticles of predefined sizes and prevent them from agglomerating and coarsening during chemical vapor deposition (CVD). Typically, catalyst metal nanoparticles can be sparsely distributed on inert substrates using methods such as atomic layer deposition, freeze-drying, impregnation, and hydrothermal synthesis, thus reducing the active loading. Inert substrates include mesoporous silica, porous magnesium oxide, and zeolites; spatial physical isolation and increasing the distance between particles can prevent aggregation. However, conventional impregnation methods are inefficient, and their adsorption capacities vary greatly due to the characteristics of the support itself, requiring a series of experiments to screen for optimal conditions. Hydrothermal synthesis can better control the uniformity of the reaction, but it requires strict control of reaction conditions and concentrations, making it challenging for industrial-scale production. For example, CN115999648A discloses a hydrothermal synthesis method for preparing carbon nanotube catalysts, including the following steps: dissolving a metal salt in water to prepare solution A; dissolving ammonium carbonate in water to prepare solution B; mixing solutions A and B to obtain a suspension precursor; transferring the suspension precursor into a hydrothermal reactor for hydrothermal reaction; and drying the residual liquid after cooling to obtain the catalyst. Although this method can obtain ultrafine powder with uniform particle size, which is beneficial for preparing high-quality carbon nanotubes with small diameter, the hydrothermal reaction method requires strict control of process pressure and temperature, resulting in high energy consumption and low yield, which greatly increases the preparation cost. Summary of the Invention

[0005] The primary objective of this invention is to provide a novel method for preparing cobalt-molybdenum / magnesium-aluminum metal catalysts, which can significantly improve the structural stability and catalytic performance of the catalysts.

[0006] A second objective of the present invention is to provide a cobalt-molybdenum / magnesium-aluminum metal catalyst prepared by the above method.

[0007] A third objective of this invention is to provide the application of the aforementioned cobalt-molybdenum / magnesium-aluminum metal catalyst in the preparation of carbon nanotubes.

[0008] The fourth objective of this invention is to provide a method for preparing carbon nanotubes.

[0009] Specifically, the preparation method of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by the present invention includes:

[0010] S1. A metal salt is chelated with a small molecule organic acid in a solvent, wherein the metal salt contains cobalt salt, molybdenum salt, magnesium salt and aluminum salt. The pH of the resulting chelate is adjusted to 3-7.5 and then mixed with a modifier to form a gel. The modifier is selected from at least one of propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone and chitosan.

[0011] S2. The gel is calcined to obtain a cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0012] The method for preparing carbon nanotubes provided by the present invention includes placing the above-mentioned cobalt-molybdenum / magnesium-aluminum metal catalyst into a tubular furnace reactor, heating it to the chemical vapor deposition reaction temperature under inert gas protection, and after the temperature stabilizes, introducing hydrocarbon gas to carry out the chemical vapor deposition reaction, and collecting the product to obtain carbon nanotubes.

[0013] The key to this invention lies in the use of small-molecule organic acids as chelating agents and specific modifiers such as propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and chitosan as promoters and stabilizers in the preparation process of cobalt-molybdenum / magnesium-aluminum metal catalysts. The cobalt-molybdenum / magnesium-aluminum metal oxides prepared in this way have good structural stability and catalytic performance. When used as a catalyst for the synthesis of carbon nanotubes, it can not only improve the carbon yield, but also obtain oligowalled carbon nanotubes with small diameter and high aspect ratio. The reason for this is speculated to be that using small-molecule organic acids as chelating agents helps to uniformly distribute metal ions in the sol, avoiding the agglomeration problem of metal ions in traditional methods, thereby improving the uniformity and dispersion of the catalyst's active sites, enhancing catalytic performance, and ultimately increasing yield. On the other hand, propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and chitosan can accelerate the formation of a stable gel. During subsequent drying and calcination, this stable structure helps to form cobalt-molybdenum / magnesium-aluminum metal oxides with excellent stability, improving structural stability. This improved structural stability allows the active sites in the calcined catalyst to maintain a nanostructure and be uniformly dispersed, enabling the catalytic process to fully utilize its activity, increasing the length and carbon yield of carbon nanotubes, while preventing aggregation at high temperatures, maintaining the nanoscale size, and obtaining carbon nanotubes with small diameter and high aspect ratio. Furthermore, the preparation method of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by this invention has significant advantages such as wide availability of raw materials, simple process, scalable production, and low cost, making it very suitable for industrial promotion and application, providing a new approach for the industrial production of high aspect ratio ultrafine carbon nanotubes. Attached Figure Description

[0014] Figure 1 This is a scanning electron microscope image of the ultrafine carbon nanotubes obtained in Example 1. Detailed Implementation

[0015] The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by this invention includes:

[0016] S1. A metal salt and a small molecule organic acid are chelated in a solvent, and the pH of the resulting chelate is adjusted to 3-7.5 and then mixed with a modifier to form a gel; the modifier is selected from at least one of propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone and chitosan.

[0017] S2. The gel is calcined to obtain a cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0018] In this invention, in step S1, the metal salt simultaneously contains cobalt salt, molybdenum salt, magnesium salt, and aluminum salt. When the metal salt does not contain cobalt salt, the catalyst activity is low because cobalt, as the active metal, is an indispensable catalytic factor in the growth of carbon nanotubes. When the metal salt does not contain molybdenum salt, the conversion rate of carbon nanotubes is low because molybdenum not only has a synergistic catalytic effect, promoting carbon atom deposition, but also regulates the size and distribution of active metal particles, alleviating Ostwald ripening. When the metal salt does not contain magnesium and aluminum salts, the catalyst's high-temperature structure is unstable because magnesium and aluminum can act as supports to load and disperse the active metal, preventing the aggregation of active metal particles at high temperatures. Simultaneously, they can also have a synergistic effect, constructing a stable spinel structural framework and fully utilizing the activity of the active metal. The preferred molar ratio of the cobalt salt, magnesium salt, and aluminum salt is (5-x):x:2. x is 4-4.8, specifically 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, or any value between them. When the molar ratio of cobalt salt, magnesium salt, and aluminum salt is controlled at (5-x):x:2 and x is 4-4.8, the resulting catalyst exhibits high activity and good stability. This is because the proportion of active metal is relatively low, allowing it to be uniformly dispersed in the bimetallic support system as nano-sized particles, greatly improving the utilization rate of active metal and mitigating the phenomenon of active metal aggregation at high temperatures. The preferred molar ratio of molybdenum salt to cobalt salt is 1:(10-100), such as 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95, 1:100, or any value between them. When the molar ratio of molybdenum salt to cobalt salt is controlled at 1:(5-20), the resulting catalyst exhibits high activity. This is because controlling the amount of molybdenum within the aforementioned preferred range can significantly improve the catalyst activity and inhibit the high-temperature aggregation of cobalt nanoparticles, thus promoting the efficient synthesis of carbon nanotubes. Furthermore, the metal salt can specifically be selected from at least one of metal nitrates, citrates, hydrochlorides, and sulfates. Furthermore, the total concentration of the metal salt in the chelation reaction system is preferably 1-5 mol / L, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 mol / L or any value between them. Additionally, the solvent can be water or a mixture of water and an organic solvent. Examples of organic solvents include methanol and / or ethanol.

[0019] This invention utilizes a sol-gel method with small-molecule organic acids as chelating agents to prepare cobalt-molybdenum / magnesium-aluminum metal catalysts. After pH adjustment, these catalysts effectively bind with metal ions to form stable chelates. This facilitates the uniform distribution of metal ions in the sol, preventing metal ion aggregation and thus improving the uniformity and dispersion of active sites on the catalyst. Consequently, a catalyst with high structural stability and catalytic performance is obtained. The preferred molar ratio of the small-molecule organic acid to the metal salt is 1:(2-6), such as 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, or any value between them. When the molar ratio of the small-molecule organic acid to the metal salt is controlled at 1:(2-6), it is more conducive to the uniform distribution of active metals in the catalyst because the functional groups of the organic acid can chelate with metal cations, thereby achieving the effect of dispersing metal sites. The small molecule organic acid is particularly preferred from at least one of malic acid (MA), citric acid (CA), glycolic acid (GA) and tartaric acid (TA).

[0020] In this invention, in step S1, the conditions for the chelation reaction preferably include a temperature of 25℃-35℃, such as 25℃, 28℃, 30℃, 32℃, 35℃ or any value between them; and a time of 0.5h-1h, such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or any value between them.

[0021] In this invention, in step S1, before mixing with the modifier, the pH of the chelate product must be adjusted to 3-7.5. If the pH of the chelate product is below 3 or above 7.5, it is difficult to form a gel; only by controlling the pH to 3-7.5 can a uniform and stable gel be formed. Specifically, the pH can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, or any value between them. Adjusting the pH of the chelate product to 3-7.5 is generally done by adding an acid or alkali solution to the chelate product. The acid solution can include at least one of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid. The alkali solution can include a mixed aqueous solution of at least one of sodium hydroxide, sodium carbonate, ammonia, ammonium carbonate, and ammonium bicarbonate.

[0022] In this invention, in step S1, the modifier accelerates the formation of a stable gel. During subsequent drying and calcination, this stable structure helps form a cobalt-molybdenum / magnesium-aluminum metal oxide with excellent stability, improving structural stability. The modifier is selected from at least one of propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and chitosan. The molar ratio of the modifier to the metal salt is preferably (0.2-1):1, such as 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, or any value between them. When the molar ratio of the modifier to the metal salt is controlled at (0.2-1):1, it promotes the formation of a stable gel because these modifiers can participate in cross-linking reactions or react with other molecules to construct a three-dimensional network structure.

[0023] In this invention, in step S2, the calcination conditions preferably include a temperature of 550℃-650℃, such as 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃ or any value between them; and a time of 30min-60min, such as 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value between them.

[0024] The present invention also provides a cobalt-molybdenum / magnesium-aluminum metal catalyst prepared by the above method.

[0025] The present invention also provides the application of the cobalt-molybdenum / magnesium-aluminum metal catalyst in the preparation of carbon nanotubes.

[0026] Furthermore, this invention also provides a method for preparing carbon nanotubes. This method includes placing the aforementioned cobalt-molybdenum / magnesium-aluminum metal catalyst into a tubular furnace reactor, heating to the chemical vapor deposition (CVD) reaction temperature under inert gas protection, and after the temperature stabilizes, introducing hydrocarbon gas to carry out the CVD reaction, collecting the product to obtain carbon nanotubes. The main improvement of this invention lies in using a specific cobalt-molybdenum / magnesium-aluminum metal catalyst in the CVD preparation of carbon nanotubes. The CVD reaction process and conditions are the same as in existing technologies, which will be known to those skilled in the art and will not be elaborated here.

[0027] The present invention will be described in detail below through examples.

[0028] Example 1 Preferred Example

[0029] This embodiment illustrates the preparation of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by the present invention. The specific process includes the following steps:

[0030] S1: Dissolve 23.5 g (0.04 mol) cobalt citrate dihydrate, 53.8 g (0.21 mol) magnesium nitrate hexahydrate, 37.5 g (0.1 mol) aluminum nitrate nonahydrate, 0.05 g (0.004 mol) ammonium molybdate tetrahydrate and 15.8 g (0.1178 mol) malic acid completely in 100 mL of deionized water. Stir continuously at 30 °C for 30 min. Then slowly add 15% ammonia solution to the resulting mixture while continuously stirring at a constant temperature and monitoring the pH. Stop adding ammonia solution when the pH reaches 4.0. Then add 9.6 g (0.17 mol) propylene oxide and stir at a constant temperature of 50 °C until the solution forms a stable gel.

[0031] S2: Disperse the gel in a crucible and calcine it at 600℃ for 60 minutes to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0032] Example 2 Preferred Example

[0033] This embodiment illustrates the preparation of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by the present invention. The specific process includes the following steps:

[0034] S1: Dissolve 29.4 g (0.05 mol) cobalt citrate dihydrate, 51.2 g (0.2 mol) magnesium nitrate hexahydrate, 37.5 g (0.1 mol) aluminum nitrate nonahydrate, 0.05 g ammonium molybdate tetrahydrate (0.004 mol), and 12.5 g (0.0651 mol) citric acid completely in 100 mL of deionized water. Stir continuously at 30 °C for 30 min. Then, slowly add 15% ammonia solution to the resulting mixture while continuously stirring at a constant temperature and monitoring the pH. Stop adding ammonia solution when the pH reaches 3.5. Then add 9.6 g (0.17 mol) propylene oxide and stir at a constant temperature of 65 °C until the solution forms a stable gel.

[0035] S2: Disperse the gel in a crucible and calcine it at 600℃ for 60 minutes to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0036] Example 3 Preferred Example

[0037] This embodiment illustrates the preparation of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by the present invention. The specific process includes the following steps:

[0038] S1: Dissolve 23.5 g (0.04 mol) cobalt citrate dihydrate, 53.8 g (0.21 mol) magnesium nitrate hexahydrate, 37.5 g (0.1 mol) aluminum nitrate nonahydrate, 0.05 g (0.004 mol) ammonium molybdate tetrahydrate and 8.9 g (0.1170 mol) glycolic acid completely in 100 mL of deionized water. Stir continuously at 30 °C for 30 min. Then slowly add 15% ammonia solution to the resulting mixture while continuously stirring at a constant temperature and monitoring the pH. Stop adding ammonia solution when the pH reaches 6.5. Then add 9.6 g (0.17 mol) propylene oxide and stir at a constant temperature of 50 °C until the solution forms a stable colloid.

[0039] S2: Disperse the gel in a crucible and calcine it at 600℃ for 60 minutes to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0040] Example 4 Preferred Example

[0041] This embodiment illustrates the preparation of the cobalt-molybdenum / magnesium-aluminum metal catalyst provided by the present invention. The specific process includes the following steps:

[0042] S1: Dissolve 23.5 g (0.04 mol) cobalt citrate dihydrate, 53.8 g (0.21 mol) magnesium nitrate hexahydrate, 37.5 g (0.1 mol) nitric acid nonahydrate, 0.05 g (0.004 mol) ammonium molybdate tetrahydrate and 17.5 g (0.1166 mol) tartaric acid completely in 100 mL of deionized water. Stir continuously at 30 °C for 30 min. Then slowly add 15% ammonia solution to the resulting mixture while continuously stirring at a constant temperature and monitoring the pH. Stop adding ammonia solution when the pH reaches 6. Then add 9.6 g (0.17 mol) propylene oxide and stir at a constant temperature of 80 °C until the solution forms a stable colloid.

[0043] S2: Disperse the gel in a crucible and calcine it at 600℃ for 60 minutes to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0044] Example 5 Preferred Example

[0045] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of propylene oxide added was 4.1 g (0.07 mol), that is, the molar ratio of propylene oxide to metal salt was 0.2:1. The other conditions were the same as in Example 1, and the cobalt-molybdenum / magnesium-aluminum metal catalyst was obtained.

[0046] Example 6 Preferred Example

[0047] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of propylene oxide added was 20.35 g (0.3504 mol), that is, the molar ratio of propylene oxide to metal salt was 1:1. The other conditions were the same as in Example 1, and the cobalt-molybdenum / magnesium-aluminum metal catalyst was obtained.

[0048] Example 7 Preferred Example

[0049] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that propylene oxide was replaced with the same molar amount of polyvinyl alcohol (purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 9002-89-5), and the other conditions were the same as in Example 1, thus obtaining the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0050] Example 8 Preferred Example

[0051] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that propylene oxide was replaced with the same molar amount of polyethylene glycol (purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 26403-72-5), and the other conditions were the same as in Example 1, thus obtaining the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0052] Example 9 Preferred Example

[0053] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that propylene oxide was replaced with the same molar amount of chitosan (purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 9012-76-4), and the other conditions were the same as in Example 1, to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0054] Example 10 Preferred Example

[0055] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that propylene oxide was replaced with the same molar amount of polyvinylpyrrolidone (purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 9003-39-8), and the other conditions were the same as in Example 1, to obtain the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0056] Example 11 (Non-Preferred Example)

[0057] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of propylene oxide added was 2.05 g (0.035 mol), that is, the molar ratio of propylene oxide to metal salt was 0.1:1. The amount of propylene oxide was lower than the preferred range, and the other conditions were the same as in Example 1, thus obtaining the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0058] Example 12 is a non-preferred example.

[0059] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of propylene oxide added was 40.7 g (0.7008 mol), that is, the molar ratio of propylene oxide to metal salt was 2:1. The amount of propylene oxide was higher than the preferred range. The other conditions were the same as in Example 1, and the cobalt-molybdenum / magnesium-aluminum metal catalyst was obtained.

[0060] Example 13 is a non-preferred example.

[0061] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of malic acid added was 46.9 g (0.3498 mol), that is, the molar ratio of small molecule organic acid to metal salt was 1:1, and the amount of small molecule organic acid was higher than the preferred range. The other conditions were the same as in Example 1, and the cobalt-molybdenum / magnesium-aluminum metal catalyst was obtained.

[0062] Example 14 is a non-preferred example.

[0063] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of malic acid added was 4.69 g (0.035 mol), that is, the molar ratio of small molecule organic acid to metal salt was 1:10, and the amount of small molecule organic acid was lower than the preferred range. The other conditions were the same as in Example 1, and the cobalt-molybdenum / magnesium-aluminum metal catalyst was obtained.

[0064] Example 15 is a non-preferred example.

[0065] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that the amount of cobalt citrate dihydrate was 0.21 mol and the amount of magnesium nitrate hexahydrate was 0.04 mol, and the other conditions were the same as in Example 1, thus obtaining the cobalt-molybdenum / magnesium-aluminum metal catalyst.

[0066] Comparative Example 1

[0067] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that cobalt citrate dihydrate was replaced with the same molar amount of magnesium nitrate hexahydrate, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0068] Comparative Example 2

[0069] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that magnesium nitrate hexahydrate was replaced with the same molar amount of cobalt citrate dihydrate, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0070] Comparative Example 3

[0071] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that aluminum nitrate nonahydrate was replaced with the same molar amount of cobalt citrate dihydrate, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0072] Comparative Example 4

[0073] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that ammonium molybdate tetrahydrate was replaced with the same molar amount of cobalt citrate dihydrate, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0074] Comparative Example 5

[0075] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that malic acid was replaced with the same molar amount of cobalt citrate dihydrate, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0076] Comparative Example 6

[0077] The cobalt-molybdenum / magnesium-aluminum metal catalyst was prepared according to the method of Example 1, except that propylene oxide was replaced with the same molar amount of malic acid, and the other conditions were the same as in Example 1, to obtain the reference metal catalyst.

[0078] Test Case

[0079] The cobalt-molybdenum / magnesium-aluminum metal catalysts obtained in the above embodiments and the reference metal catalysts obtained in the comparative examples were respectively laid in ceramic boats. The ceramic boats were then placed in a tube furnace, and the temperature was increased to 700°C at a rate of 15°C / min under nitrogen protection at a flow rate of 2000 sccm. After the temperature stabilized, propylene (1200 sccm) was introduced and reacted for 60 min. The propylene introduction was then stopped, and the mixture was cooled to room temperature under nitrogen protection to obtain carbon nanotubes. The weight, carbon yield, average diameter, average aspect ratio, and specific surface area of ​​the obtained carbon nanotubes are shown in Table 1. Wherein, carbon yield = (mass of carbon nanotubes / mass of catalyst) × 100%.

[0080] Table 1

[0081]

[0082]

[0083] As shown in Table 1, the cobalt-molybdenum / magnesium-aluminum metal catalyst obtained by the method provided in this invention can not only effectively improve the carbon yield of carbon nanotubes, but also reduce the diameter of carbon nanotubes and increase their aspect ratio. The carbon nanotubes corresponding to the cobalt-molybdenum / magnesium-aluminum metal catalyst obtained in Example 1 are shown in Table 1. Figure 1 .from Figure 1 It can be seen that carbon nanotubes have a small diameter and good uniformity.

[0084] A comparison of Examples 1 and 11-14 shows that when the molar ratio of modifier to metal salt is controlled within the preferred range, and when the molar ratio of small molecule organic acid to metal salt is controlled within the preferred range, it is more conducive to improving the carbon yield of carbon nanotubes. At the same time, it can further reduce the diameter of carbon nanotubes and increase the aspect ratio.

[0085] A comparison of Examples 1 and 15 shows that when the molar ratio of cobalt salt, magnesium salt and aluminum salt is controlled at (5-x):x:2 and x is 4-4.8, it is more conducive to further reducing the diameter of carbon nanotubes and further increasing the aspect ratio.

[0086] As can be seen from the comparison between Example 1 and Comparative Example 1, when the metal salt does not contain cobalt salt, the catalyst activity is low, and the carbon yield, aspect ratio and specific surface area of ​​carbon nanotubes will decrease significantly, while the tube diameter will increase significantly.

[0087] As can be seen from the comparison between Example 1 and Comparative Examples 2 and 3, when the metal salt does not contain magnesium or aluminum salt, the carbon yield, aspect ratio and specific surface area of ​​the obtained carbon nanotubes will decrease to a certain extent, while the tube diameter will increase.

[0088] As can be seen from the comparison between Example 1 and Comparative Example 4, when the metal salt does not contain ammonium salt, the carbon yield, aspect ratio and specific surface area of ​​the obtained carbon nanotubes decrease significantly, while the tube diameter also increases.

[0089] As can be seen from the comparison between Example 1 and Comparative Example 5, when no organic acid is used in the catalyst preparation process, the carbon yield, aspect ratio and specific surface area of ​​the obtained carbon nanotubes will decrease significantly, while the tube diameter will increase significantly.

[0090] As can be seen from the comparison between Example 1 and Comparative Example 6, when no modifier is used in the catalyst preparation process, the carbon yield, aspect ratio and specific surface area of ​​the obtained carbon nanotubes will decrease significantly, and the tube diameter will also increase.

[0091] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.

Claims

1. A method for preparing a cobalt-molybdenum / magnesium-aluminum metal catalyst, characterized in that, The method includes: S1. A metal salt is chelated with a small molecule organic acid in a solvent, wherein the metal salt contains cobalt salt, molybdenum salt, magnesium salt and aluminum salt. The pH of the resulting chelate is adjusted to 3-7.5 and then mixed with a modifier to form a gel. The modifier is selected from at least one of propylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone and chitosan. S2. The gel is calcined to obtain a cobalt-molybdenum / magnesium-aluminum metal catalyst.

2. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, In step S1, the molar ratio of the cobalt salt, magnesium salt and aluminum salt is (5-x):x:2, where x is 4-4.8; the molar ratio of the molybdenum salt to the cobalt salt is 1:(5-20).

3. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, The total concentration of metal salts in the chelation reaction system is 1-5 mol / L; The metal salt is selected from at least one of nitrates, citrates, hydrochlorides, and sulfates.

4. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, The molar ratio of the small molecule organic acid to the metal salt is 1:(2-6).

5. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, The small molecule organic acid is selected from at least one of malic acid, citric acid, glycolic acid, and tartaric acid.

6. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, In step S1, the chelation reaction conditions include a temperature of 25℃-35℃ and a time of 0.5h-1h. Preferably, the molar ratio of the modifier to the metal salt is (0.2-1):

1.

7. The method for preparing the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 1, characterized in that, In step S2, the calcination conditions include a temperature of 550℃-650℃ and a time of 30min-60min.

8. A cobalt-molybdenum / magnesium-aluminum metal catalyst prepared by the method according to any one of claims 1-7.

9. The application of the cobalt-molybdenum / magnesium-aluminum metal catalyst according to claim 8 in the preparation of carbon nanotubes.

10. A method for preparing carbon nanotubes, characterized in that, The method includes placing the cobalt-molybdenum / magnesium-aluminum metal catalyst of claim 8 into a tubular furnace reactor, heating it to the chemical vapor deposition reaction temperature under inert gas protection, and after the temperature stabilizes, introducing hydrocarbon gas to carry out the chemical vapor deposition reaction, and collecting the product to obtain carbon nanotubes.

Citation Information

Cited By

  • Catalyst for preparing carbon nanotubes and preparation method thereof

    CN121490777A

  • A catalyst for preparing carbon nanotubes and a method for preparing the same

    CN121490777B